PERAN PROFITABILITAS DALAM MEMODERASI PENGARUH STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2020)
This study aims to determine the effect of capital structure and dividend policy on firm value by moderating profitability in food & beverages companies. Samples are Food & Beverages Sub Sector manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period, which were taken using purposive sampling technique. The analysis technique used is a moderation regression analysis (MRA) using eviews 9. The results of hypothesis testing show that the capital structure variable (DER) has a positive and significant effect on firm value (PBV), dividend policy (EPS) has a positive and significant effect on firm value ( PBV), profitability (ROA) strengthens the effect of capital structure (DER) on firm value (PBV), but profitability (ROA) does not strengthen the effect of dividend policy (EPS) on firm value (PBV). These results indicate that the higher the capital structure financed by debt and the greater the dividends distributed to investors, the higher the firm value.Keywords: Capital Structure, Dividend Policy, Profitability, Firm Value